Stimulation of Staphylococcus aureus Ligase Enzyme by Magnesium Ion - Arqam Mohamad Alomari1 , Aseel A. H. Al-Layla2 , Ibrahim Faris Ali3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Ligases enzymes were discovered as a member of the nucleotidyl transferase family. Here in this paper, DNALigase is extracted from S. aureus works with the cofactor NAD+ to make a phosphodiester bond and reformbetween the 3’hydroxyl and 5’phosphate DNA end. Staphylococcus aureus-DNA Ligases Enzyme type A(SLE-A) contains two essential domains; NTase and OB- fold domain, which are the most essential domainsfor the enzyme function. The main aim of the study is to investigate the activity of SLE-A in the presenceof magnesium ion (Mg+2) by evaluating several kinetic parameters on a time course. The result showed thatSLE-A has optimal activity at 500 µM of Mg+2. Furthermore, the low number of Equilibrium AssociationConstant (Km value) explains the binding affinity between DNA ligase of Staphylococcus aureus SLE-Aenzyme and Mg+2 ion was very high and sold.